A (re)produção do espaço urbano no município de Pacaraima - 1995-2013 - Tácio José Natal Raposo (2015)
The Production of the Space from Pacaraima city in Amazonian context in their different approaches can be analyzed based on its geo-history as a product of socio-spatial relations of its producers space agents. It is considered that this production keeps an indigenous ancestry, passing through the miners action, military, village administrators, mayors, public policy and big federal government intervention thus showing the forces of horizontality and verticality of production spatial. Thus, the present analyzes the production of space of the Pacaraima city considering the location and the processes in the production of space specifically looking at the period from 1973 to 2013. The clipping shows the beginning of the assemblage process of people in the area where the city is located with the formation of the Village of Division. This period lasts for ten years and is marked by a strong military presence in the region until the creation of BV8 Village or Pacaraima Village in 1983. During the establishment period of the Village made a study of its managers performance as spatial agents, until the establishment of the city in 1995 and its first legislature in 1997. The analysis of spatial production process of Pacaraima as a city is make by the analysis of sets of actions and measures adopted by each mayor as a municipal executive protagonist. Analyzes even the forces of vertical public policies and the forces fields, power spaces understood as horizontal forces while spatial producers agents. Was used qualitative and quantitative method that echoes in a analytical multiplicity perspectives on the same phenomenon of spatial production. The techniques of documentary bibliographical research, interviews were enriched with integrative review technique and production of maps. This work cooperate with seizure of complex events and processes that made possible the genesis and the spatial re-production of Pacaraima city.